Brain rules for baby: How to raise a smart and happy child from zero to five - Medina, John (Washington : Pear Press, 2010)
What's the single most important thing you can do during pregnancy? What does watching TV do to a child's brain? What's the best way to handle temper tantrums? Scientists know. In his New York Times bestseller Brain Rules, Dr. John Medina showed us how our brains really work, and why we ought to redesign our workplaces and schools. Now, in Brain Rules for Baby, he shares what the latest science says about how to raise smart and happy children from zero to five. This book is destined to revolutionize parenting. Just one of the surprises: The best way to get your children into the college of their choice? Teach them impulse control. Brain Rules for Baby bridges the gap between what scientists know and what parents practice. Through fascinating and funny stories, Medina, a developmental molecular biologist and dad, unravels how a child's brain develops and what you can do to optimize it. You will view your children, and how to raise them, in a whole new light. You'll learn: Where nature ends and nurture begins. Why men should do more household chores. What you do when emotions run hot affects how your baby turns out, because babies need to feel safe above all. TV is harmful for children under 2Your child's ability to relate to others predicts her future math performance. Smart and happy are inseparable. Pursuing your child's intellectual success at the expense of his happiness achieves neither. Praising effort is better than praising intelligence. The best predictor of academic performance is not IQ. It's self-control. What you do right now--before pregnancy, during pregnancy, and through the first five years--will affect your children for the rest of their lives. Brain Rules for Baby is an indispensable guide.
Keywords: Brain Development -- Parenting -- Psychology